Effect of the carbonate environment on morphology and sintering behaviour of variously co-doped (Ca, Sr, Er, Pr) Samarium-doped Ceria in co-precipitation/hydrothermal synthesis. Issue 15 (15th October 2018) - Dell'Agli, G.; Spiridigliozzi, L.; Pansini, M.; Accardo, G.; Yoon, S.P.; Frattini, D.
Abstract: Variously co-doped Samaria-20 mol% doped ceria (SDC20) nanopowders were synthesized through a combined co-precipitation/hydrothermal treatment method under different carbonate environments. Urea and ammonium carbonate were used as both precipitating and mineralizing agent. In all cases, the adopted powder composition was Ce0.8 Sm0.16 ×0.04 O1.9-δ, where X was either Ca, Sr, Er or Pr and δ is 0 for trivalent cations (i.e. Er and Pr) or 0.02 for divalent cations (i.e. Ca and Sr). The effects of different synthesis parameters on powders morphology and crystalline phases have been pointed out. Differently synthesized powders underwent structural and morphological transformations during the hydrothermal treatment leading to different crystalline precursors for the desired co-doped ceria nanopowders, i.e. crystallized into the fluorite-like cubic structure after a calcination step at 700 °C for 1 h. The final properties of the calcined powders are strongly related to the corresponding parent powder features, consequently determining different sintering behaviours in the various pellets. In particular, except for Er/Sm co-doped ceria, all samples synthesized with ammonium carbonate as precipitating/mineralizing agent exhibited excellent sintering behaviour, with remarkable values of relative density (higher than 97% and up to 99.4%) and an almost ideal microstructure. Definitely, the present work gives several guidelines in terms of synthesis parameters and conditions to produce, with a relatively simple and cheap process, highly reactive co-doped ceria nanopowders with tuned properties and suitable as electrolytes for intermediate temperature solid oxide fuel cells (IT-SOFCs).